2018
DOI: 10.1016/j.livsci.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of stocking rate and prolificacy potential on profitability of grass based sheep production systems

Abstract: Investigating the role of stocking rate and prolificacy potential on profitability of grass based sheep production systems, Livestock Science,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
(44 reference statements)
3
22
0
Order By: Relevance
“…Maximising the number of lambs born per ewe per year is a key factor in profitable and sustainable sheep production [20], however the issue of dietary deficiency of nutrient supply is magnified with ewes of high prolificacy. With increased ewe prolificacy, the nutrient requirements, in particular the energy required by the ewe, also increases [21] during late pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Maximising the number of lambs born per ewe per year is a key factor in profitable and sustainable sheep production [20], however the issue of dietary deficiency of nutrient supply is magnified with ewes of high prolificacy. With increased ewe prolificacy, the nutrient requirements, in particular the energy required by the ewe, also increases [21] during late pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%
“…When grazed herbage is compared to silage and concentrates, its cost of production is in the ratio of 1:1.8:2.4 respectively (Finneran et al., ). Herbage can supply up to 95% of the energy requirements of sheep (with the other 5% accounting for supplementation to ewes pre‐lambing; Davies & Penning, ), providing sheep producers in temperate regions of the world an opportunity to maximize output from herbage through increased herbage dry‐matter (DM) production and utilization (Bohan et al., ; Keady, Hanrahan, & Flanagan, ). Achieving a balance between the supply of high‐quality herbage and herbage utilization is paramount in optimizing temperate grass‐based lamb production systems (Earle et al., ); however, this remains a challenge for many producers.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with those published by Simplí cio & Azevedo (2014), who emphasised that the profitability by ewes and area unit exploration is influenced by the number of offspring marketed and incorporated into the herd as replacement animals. Bohan et al (2018) found that the main drivers of profitability were the number of lambs weaned per ha, related to the growth and utilisation of pastures, since the animals of this simulation were also considered to be grazing.…”
Section: Discussionmentioning
confidence: 99%